Rumah Tinggal Berbasis Green Building di Kota Denpasar - Ratih Yulianasari, A. A. Ayu Sri (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2017)
A comforting home does not simply refer to a beautifully designed and built form, but it is also about involving environmentally conscious decisions. A great challenge faces many cities, such as Denpasar, nowadays is how to impose and implement green architecture related concepts and practices, thus the progressive housing developments taking place in many urban areas all over the world incur less (no) destruction to nature. The green architecture idealism comes under the umbrella of a greater concept of sustainable development. It aims at reducing negative impacts brought by any form of development on the built forms, human health and ultimately on our natural environment. This research uses qualitative-descriptive approach. Data collection was done using several methods, which are interviews with developers, site observations, and literature study. The purpose of this research is to develop environmentally friendly solutions in overcoming problems associated to housing developments in Denpasar City. Study results reveal that such solutions can be applied in four manners, such as: (i) efficiency and energy savings by adjusting windows positions and the installment of additional ventilations; (ii) water conservation, i.e. by planting grass as a media to cover the soil and create a rain garden; (iii) the use of recycled materials, for example by using building debris as materials for ground coverage; (iv) creation of healthy and comfortable living space by reducing indoor partitions, the use of bright colors but have shading effects, especially to ones' eyes, high ceiling, and nature friendly waste management mechanisms and practices. Keywords: house, green architecture, environmentally friendly, Denpasar